(untitled) (Revista de História da UEG (REVHIST), 2025)
This article seeks to explore a "parallax" of the Atlantic, focusing on the Indigenous perception, an aspect rarely explored of the ocean and the narrowing of connections between continents from the 15th and 16th centuries onwards. To achieve this, a bibliographic review will be conducted along with the analysis of documentaries, images, songs, and legends to examine the distinct worldviews that shaped interactions in this space. Mythological, cultural, historical, and especially economic aspects will be considered, as the pursuit of wealth and domination appeared to be the ultimate European objective, driving their inquisitive approach to this process. The objective is to understand how Indigenous perspectives contributed to constructing complex and often contradictory meanings of the Atlantican Ocean that simultaneously serves as a space of encounter and confrontation. Overcoming Eurocentrism requires the deconstruction of its foundations and the development of a new knowledge framework that values cultural diversity and historical plurality. Keywords: Atlantic History, African Diaspora, Indigenous Resistance.